Património Arqueológico no concelho de Mora: um exemplo de gestão - Rocha, Leonor (2018)
Mora municipality stands out in Portugal for its pioneering archaeological research. In fact, at a time when most of the work carried out were casuistic, spatial and chronologically scattered, Pavia parish had a structured research project, conducted by Virgilio Correia, between 1914 and 19182. After being caught by the residually work done by Manuel Heleno in Central Alentejo, in the 30s, the area around gained importance in the last decade of that century when they begin new archaeological work, inserted in continuing research projects. Over the past 20 years we have proceeded to an inventory process, excavation of megalithic monuments, surveys in settlements, recovery and musealization of archaeological sites ...Commemorating the 100th anniversary of the beginning of the investigation, the county moved to a new project which results in an example of good asset management, the result of a long investment: the creation of a Museum of Megalithism.